WINTER WHEAT FERTILIZING IN THE CONDITIONS OF CHZ OF TAMBOV REGION - L. N. Vislobokova; O. M. Ivanova (Зерновое хозяйство России)
The results of long-year experiments with mineral and organic fertilizing in the conditions of long-term stationary fields experiment have been given. A great number of experiments showed influence of different systems of fertilizing in field grain crop rotation on the elements of soil fertility, productivity and quality of winter wheat varieties in the conditions of ChZ of Tambov region. It has been revealed that the largest yields of grain were received in all variants of the experiment where fertilizing was applied in comparison with those where there was no any fertilizing. Mineral and organic fertilizing improves productivity and grain quality. Maximum productivity of variety ‘Mironovskaya 808’ (4,04 t/ha) was achieved with the use of NPK + manure 30t/ha, equivalent to 2 norms of NPK. Productivity of new winter wheat varieties ‘Moskovskaya 39’ and ‘Gubernator Dona’ was the greatest one in all experiments conducted in 2008-2013. The highest increase of productivity (1,05 t/ha) was noted in the case with application of NPK, 2 norms of N80P80K80. Together with productivity increase it’s necessary to pay attention to improvement of grain quality. Protein content is the most important trait of grain quality. Wheat cultivar ‘Mironoskaya 808’ is characterized with a lower content of raw protein. The least value (12,6%) was received in the cultivars without fertilizing.  There was no essential difference among the cultivars which were fertilized. During 2008-2013 years the content of raw protein was higher than that of the variety ‘Mironoskaya 808’. There was no essential difference among the cultivars, some increase of content of raw protein (14,6 %) was noted in the case with application of NPK, 2 norms of N80P80K80 compared with the case without fertilizing. The basic agro chemical traits have been considered in the article; fertilizing effects on soil fertility components after a cycle of seven crop rotation were shown. During 42 years of experimenting humus content was reduced in all variants of the experimenting; content of moving phosphorus in soil was increased due to fertilizing; content of exchangeable potassium didn’t change greatly remaining on a rather high level.